Life Skills Approach in Arabic Language Learning at Islamic Boarding School-Based Madrasah Aliyah - Atabik, Atabik; Yahya, M. Slamet; Mustajab, Mustajab (Letiges, 2023)
This study aimed to find a life skills approach to learning Arabic in Islamic boarding schools based on Islamic high schools. This research is field research using qualitative methods. The location of this research is the Islamic boarding school-based Madrasah Aliyah. Using the form of observation, interviews and documentation in collecting data. As for analyzing the data, researchers carried out several stages of analysis, starting from data collection, reduction, review and evaluation. The results of this study cover two aspects, namely first, the Arabic language learning curriculum implemented in MA Salafiyah and MA Darussangadah is an integrated curriculum between the curriculum of the Ministry of Religion and the curriculum of Islamic boarding schools, based on classical studies and modern books with a language learning orientation. Arabic language actively or passively. Second, the Arabic language learning model at Madrasah Aliyah is based on Islamic boarding schools in Kebumen Regency, namely (1) Arabic learning at MA Salafiyah Wonoyoso is more oriented towards maharah lughawiyah (istima', kalam, qira'ah, and kitabah) as the basis of student competence. The process of learning Arabic is taught by integrating the four maharah lugawiyah through learning Arabic subjects, religious subjects, and linguistic practices in Islamic boarding schools; (2) Learning Arabic at MA Darussangadah develops learning Arabic that is oriented towards active and passive communication skills. This active communication skill is the skill of using spoken and written language. At the same time, the passive ability is the skill of understanding Arabic reading and other people's speech.